Police Collapse in Authoritarian Regimes: Lessons from Tunisia. (3rd October 2017) - Mekouar, Merouan
ABSTRACT: The quick unraveling of authoritarian systems specifically designed to bear social pressure during revolutions is puzzling. Building on the 2011 Tunisian revolution, this article analyzes the collapse of the police apparatus during the 2011 revolution. In line with Way and Levitsky's study of authoritarian collapse, this article shows that the low cohesion and low scope of the security forces is one of the main factors explaining the rapid collapse of one of the Arab world's seemingly most solid repressive systems. At the theoretical level, this article will demonstrate that preference falsification is a double-edged sword. On the one hand, it can nourish authoritarian resilience. On the other, it can also weaken repressive regimes by making core members of the regime overestimate the loyalty of the low-ranking members of the security apparatus.